2021
DOI: 10.3390/ijerph18189541
|View full text |Cite
|
Sign up to set email alerts
|

Association between Financial Hardship and Symptom Burden in Patients Receiving Maintenance Dialysis: A Systematic Review

Abstract: Background: Many patients on maintenance dialysis experience financial hardship. Existing studies are mainly cost analyses that quantify financial hardship in monetary terms, but an evaluation of its impact is also warranted. This review aims to explore the definition of financial hardship and its relationship with symptom burden among patients on dialysis. Methods: A literature search was conducted in November 2020, using six electronic databases. Studies published in English that examined the associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 93 publications
(234 reference statements)
1
7
1
Order By: Relevance
“…KTRs with a per capita monthly income of 2000-6000 are more likely to be in the all-high subgroup. Such results are similar to those of previous research 50 that proved that poor financial burden can increase the symptom burden. Having a better financial situation will encourage KTRs to choose a better lifestyle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…KTRs with a per capita monthly income of 2000-6000 are more likely to be in the all-high subgroup. Such results are similar to those of previous research 50 that proved that poor financial burden can increase the symptom burden. Having a better financial situation will encourage KTRs to choose a better lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…52 Patients who are facing significant financial difficulties may be less likely to seek medical attention or follow through with treatment, which can ultimately lead to more severe symptoms. 50 It's worth mentioning that the study revealed some surprising results. It was found that having a per capita monthly income of less than 2,000 was not a predictor of this particular segment.…”
Section: Discussionmentioning
confidence: 88%
“…There is abundant evidence of the impact of low socioeconomic status on patients with ESRD (Billington et al, 2008;He, 2012;Zhang and Xue, 2011). While our previous systematic review (Ng et al, 2021) identified associations between financial difficulties and both physical and mental well-being, the present study showed that socioeconomic status may specifically affect hope. The finding related to the PD submodality is consistent with some previous reports (Bieber et al, 2014).…”
Section: Discussioncontrasting
confidence: 83%
“…Patients in MHD suffered from long-term hemodialysis-related treatment, which further increases the burden of nance, physical pain, social-psychological stress. A large number of studies have demonstrated that depression, anxiety, and nancial hardship were associated with fatigue (IDF and PDF) in MHD patients [29,30,31]. High resilience level may help MHD patients to face these challenges with positive attitude, which have been reported in other healtion conditions, such as mild traumatic brain injury [32], stroke [33], indicated fatigue was associated with resilience.…”
Section: Discussionmentioning
confidence: 88%